A study on extraction and determination of some properties of Spirulina extracts - Tuan, Hoang Van; Son, Pham Huong; Thuy, Pham Thu (Academia Journal of Biology, 2012)
The purpose of this study is establish a simple method for obtaining extracts containing soluble bioactive from Sprulina algae. Determination of functional properties of extracts to give the basis to apply for the production of functional beverage. The cyanobacterium Spirulina platensis has been considered to be an important subject for biotechnological research due to its nutritional importance. S. platensis is a blue-green microalgae which can produce large quantities of high value products such as beta carotene, phycoyanin, chlorophyll, gama linolenic acid… In this study, various solvents for included methanol, ethanol, hexane and water were used to select extracted solvent obtaining aqueous extracts from Spirulina algae. The process of extraction was done by two methods: Soaking, freezing and thawing. The extracts were tested antioxidant activity by free radicals scavenging capacity and antimicrobial activity. The data indicated that using ethanol 55%, the rate of biomass/solvent is 5 g/100 ml. The freezing and thawing extraction method  with freezing time (Ft) in 2 hours, thawing cycle in 4 times gave the highest result. Phycocyanin level in the extract reached 2.67 mg/ml, scavenging capacity (SC) reached 65,68%; SC50 20.18 mg/ml. The extract can against six tested microorganism including E. coli, P. aeruginosa, B. subtillis, S. aureus, A. niger and S. cerevisiae.